Identification of a mechanism for increased cardiovascular risk among individuals with low vitamin D concentrations - Schnatz, Peter F. (2011)
OBJECTIVE: The aim of this study was to investigate the plasma concentrations of vitamin D and its association with plasma lipid profiles. METHODS: Plasma vitamin D(3) and lipid concentrations were measured in 119 female cynomolgus monkeys (pre-menopausal, n = 49; ovariectomized, n = 70) consuming approximately 1,000 IU per day of vitamin D(3). In a subset of the ovariectomized monkeys (n = 23), vitamin D(3) was remeasured after 6 months. The concentrations of vitamin D(3) were analyzed as a continuous variable and were divided at the median into high (≥48 ng/mL) versus low (<48 ng/mL) groupings. RESULTS: Among the 119 monkeys, the range of vitamin D(3) concentrations was 24.0 to 95.2 ng/mL (mean ± SD, 48.5 ± 12.7 ng/mL). Plasma vitamin D(3) concentration was positively associated with high-density lipoprotein cholesterol (HDL-C; P = 0.003). Monkeys in the high vitamin D(3) group had a significantly greater plasma HDL-C concentration (57.9 mg/dL) than did those in the low vitamin D(3) group (47.1 mg/dL; P = 0.001). Although the difference was not significant (P = 0.120), the monkeys in the high vitamin D(3) group had a decreased total plasma cholesterol–to–-C ratio compared with those in the low vitamin D(3) group (5.4 and 6.2, respectively), potentially putting them at lower risk of atherosclerosis development. CONCLUSIONS: Given that the monkeys all consumed a diet replete in vitamin D(3), it seems that individual differences in vitamin D absorption or metabolism may have determined whether the monkeys had high or low concentrations of vitamin D(3). Lower vitamin D(3) was associated with a more atherogenic lipid profile, a major risk factor for progressing to coronary artery atherosclerosis in monkeys and human beings.